2022
DOI: 10.1021/acssuschemeng.2c03791
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Silicon Quantum Dots Against Solar Light/Hot Water: RGB Foldable Films and Ligand Engineering

Abstract: Heavy-metal-free fluorophores such as silicon quantum dots (SiQDs) are required for next-generation light sources to address environmental concerns. However, few studies on SiQD devices are concerned with flexible devices, luminescence colors other than red, or stability data. Herein, the synthesis via three different methods of colloidal SiQDs exhibiting red/green/blue (RGB) photoluminescence (PL) is presented. The durability of each RGB SiQD embedded in a flexible polymer film (>4 × 4 cm 2 ) and exposed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 90 publications
3
34
0
Order By: Relevance
“…The corresponding PLQY is 5.1%. Previous research on Si QDs has revealed the influence of size distribution 12−14 and surface properties 15,72,73 on their optical properties. Fujimoto et al 72 The above results suggest the delicate control of discharge conditions and the size of the Si strip are conducive to from Si QDs through PWD.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The corresponding PLQY is 5.1%. Previous research on Si QDs has revealed the influence of size distribution 12−14 and surface properties 15,72,73 on their optical properties. Fujimoto et al 72 The above results suggest the delicate control of discharge conditions and the size of the Si strip are conducive to from Si QDs through PWD.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous research on Si QDs has revealed the influence of size distribution 12−14 and surface properties 15,72,73 on their optical properties. Fujimoto et al 72 The above results suggest the delicate control of discharge conditions and the size of the Si strip are conducive to from Si QDs through PWD. At the charging voltage of 7.0−8.0 kV, the Si strip completely melts and evaporates to form gas Si, which expands rapidly before the formation of plasma channel.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these emission characteristics is that the PL-decay (t PL ) is so fast, on the order of nanoseconds instead of micro -to milliseconds as typical alkyl-SiQD. 13,14 Fujimoto et al (2022) 15 elaborated on the difference between the F-band and S-band. The authors synthesized three types of SiQDs based on their emission.…”
Section: A Introductionmentioning
confidence: 99%